Botswana: Recent developments in agricultural research - Stads, Gert-Jan; Pholo, Motlalepula (International Food Policy Research Institute, 2011)
Agriculture's contribution to Botswana's gross domestic product (GDP) fell dramatically from 44 percent at independence in 1966 to less than 2 percent in 2008, mainly due the increased economic importance of mining, tourism, manufacturing, and the services industry (World Bank 2010). Despite Botswana's arid climate and the sector's declining contribution to formal employment, agriculture remains important as a source of food, income, and employment for a large proportion of the population, particularly in rural areas. Given that productivity gains are critical to maintaining and enhancing competitiveness of Botswana's commodities and advancing the status of the rural poor, agricultural research and development (R&D) should remain a top priority in national development planning. For most of the 1990s, agricultural R&D investments in Botswana increased steadily (Beintema, Modiakgotla, and Mazhani 2004).